Prevalence, self-care behaviors, and self-care activities for peripheral neuropathy symptoms of HIV/AIDS - Nicholas, Patrice K. (Nurs Health Sci, 2010)
As part of a larger randomized controlled trial examining the efficacy of an HIV/AIDS symptom management manual (n = 775), this study examined the prevalence of peripheral neuropathy in HIV-infected individuals at 12 sites in the USA, Puerto Rico, and Africa. Neuropathy was reported by 44% of the sample; however, only 29.4% reported initiating self-care behaviors to address the neuropathy symptoms. Antiretroviral therapy was found to increase the frequency of neuropathy symptoms, with an increased mean intensity of 28%. A principal axis factor analysis with Promax rotation was used to assess the relationships in the frequency of use of the 18 self-care activities for neuropathy, revealing three distinct factors: (i) an interactive self-care factor; (ii) a complementary medicine factor; and (iii) a third factor consisting of the negative health items of smoking, alcohol, and street drugs. The study’s results suggest that peripheral neuropathy is a common symptom and the presence of neuropathy is associated with self-care behaviors to ameliorate HIV symptoms. The implications for nursing practice include the assessment and evaluation of nursing interventions related to management strategies for neuropathy.